The impact of remittances on household food security: A micro perspective from Tigray, Ethiopia - Nigussie Abadi; Ataklti Techane; Girmay Tesfay; Daniel Maxwell; Bapu Vaitla (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
While the volume of remittances to developing countries has been growing significantly over the years, the impact of remittances on food security has not received much attention. To bridge the gap this paper has examined the impact of remittances on farm household's food security status, using a sample of 301 farm households from two livelihood zones of the Tigray Regional State of Ethiopia. The average treatment effect (ATT) results show that households with access to remittance have significantly lower Coping Strategy index (CSI), Reduced Coping Strategy index (rCSI) and Household Food Insecurity Access Scale (HFIAS) on average as compared to households without remittance income. However, there is no significant difference in the ATT effect of remittances on Food Consumption Score (FCS) between treated and control households. These findings suggest that remittances lower the frequency and the severity of coping strategies, and households with remittances have i) lower anxiety about not being able to procure sufficient food; ii) higher ability to secure adequate quality food; and iii) lower experience of insufficient quantity of food intake than those without remittance. Thus, it is imperative to include migration and remittances as important components of food security programs and food security policies in Ethiopia and should go beyond just food production measures, and include measures that help in generating adequate levels of effective demand via income growth or transfers policies.
Keywords: 330; remittance; coping strategy; food insecurity access scale; PSM; Ethiopia